PEMURNIAN GLUKOAMILASE DARI HASIL FERMENTASI KAPANG RHIZOPUS ORYZAE - Linar Z. Udin; Rini Noviyanti; A. Sidik; A. T. Karossi (Jurnal Kimia Terapan Indonesia, 1994)
Purification of the glucoamylase R. oryzae was carried out by addition of ammonium sulfate 80% saturation, on the fermentation broth at 4°C. The precipitate formed by centrifugation at 9000 rpm was then dialyzed in buffer solution and then concentrated using freeze dryer. It was found that the specific activity of the enzyme was around three-fold higher the crudeenzyme from fermentation broth and the purity of the enzyme was almost twelve-fold.purer than the crude enzyme. The molecular weight of the glucoamylase was found to be 36,000 as determined by SDS gel electrophoresis. The optimum pH witli soluble starch as substrate was at pH 4.5 and the optimum temperature was 55°C while the Km Value was 0.027%.